5.9.58 Problems 5701 to 5800

Table 5.743: First order ode linear in derivative

#

ODE

Mathematica

Maple

14775

\[ {}y^{\prime } = \frac {t y}{t^{2}+1} \]

14776

\[ {}y^{\prime } = -5 y+\sin \left (3 t \right ) \]

14777

\[ {}y^{\prime } = t +\frac {2 y}{t +1} \]

14778

\[ {}y^{\prime } = 3+y^{2} \]

14779

\[ {}y^{\prime } = 2 y-y^{2} \]

14780

\[ {}y^{\prime } = -3 y+{\mathrm e}^{-2 t}+t^{2} \]

14781

\[ {}x^{\prime } = -t x \]

14782

\[ {}y^{\prime } = 2 y+\cos \left (4 t \right ) \]

14783

\[ {}y^{\prime } = 3 y+2 \,{\mathrm e}^{3 t} \]

14784

\[ {}y^{\prime } = t^{2} y^{3}+y^{3} \]

14785

\[ {}y^{\prime }+5 y = 3 \,{\mathrm e}^{-5 t} \]

14786

\[ {}y^{\prime } = 2 t y+3 t \,{\mathrm e}^{t^{2}} \]

14787

\[ {}y^{\prime } = \frac {\left (t +1\right )^{2}}{\left (y+1\right )^{2}} \]

14788

\[ {}y^{\prime } = 2 t y^{2}+3 t^{2} y^{2} \]

14789

\[ {}y^{\prime } = 1-y^{2} \]

14790

\[ {}y^{\prime } = \frac {t^{2}}{y+t^{3} y} \]

14791

\[ {}y^{\prime } = y^{2}-2 y+1 \]

14792

\[ {}y^{\prime } = \left (y-2\right ) \left (y+1-\cos \left (t \right )\right ) \]

14793

\[ {}y^{\prime } = \left (y-1\right ) \left (y-2\right ) \left (y-{\mathrm e}^{\frac {t}{2}}\right ) \]

14794

\[ {}y^{\prime } = t^{2} y+1+y+t^{2} \]

14795

\[ {}y^{\prime } = \frac {2 y+1}{t} \]

14796

\[ {}y^{\prime } = 3-y^{2} \]

14979

\[ {}y^{\prime } = 3-\sin \left (x \right ) \]

14980

\[ {}y^{\prime } = 3-\sin \left (y\right ) \]

14981

\[ {}y^{\prime }+4 y = {\mathrm e}^{2 x} \]

14982

\[ {}x y^{\prime } = \arcsin \left (x^{2}\right ) \]

14983

\[ {}y y^{\prime } = 2 x \]

14989

\[ {}y^{\prime } = 4 x^{3} \]

14990

\[ {}y^{\prime } = 20 \,{\mathrm e}^{-4 x} \]

14991

\[ {}x y^{\prime }+\sqrt {x} = 2 \]

14992

\[ {}\sqrt {x +4}\, y^{\prime } = 1 \]

14993

\[ {}y^{\prime } = x \cos \left (x^{2}\right ) \]

14994

\[ {}y^{\prime } = x \cos \left (x \right ) \]

14995

\[ {}x = \left (x^{2}-9\right ) y^{\prime } \]

14996

\[ {}1 = \left (x^{2}-9\right ) y^{\prime } \]

14997

\[ {}1 = x^{2}-9 y^{\prime } \]

15001

\[ {}y^{\prime } = 40 \,{\mathrm e}^{2 x} x \]

15002

\[ {}\left (x +6\right )^{{1}/{3}} y^{\prime } = 1 \]

15003

\[ {}y^{\prime } = \frac {x -1}{1+x} \]

15004

\[ {}x y^{\prime }+2 = \sqrt {x} \]

15005

\[ {}y^{\prime } \cos \left (x \right )-\sin \left (x \right ) = 0 \]

15006

\[ {}\left (x^{2}+1\right ) y^{\prime } = 1 \]

15008

\[ {}y^{\prime } = \sin \left (\frac {x}{2}\right ) \]

15009

\[ {}y^{\prime } = \sin \left (\frac {x}{2}\right ) \]

15010

\[ {}y^{\prime } = \sin \left (\frac {x}{2}\right ) \]

15011

\[ {}y^{\prime } = 3 \sqrt {x +3} \]

15012

\[ {}y^{\prime } = 3 \sqrt {x +3} \]

15013

\[ {}y^{\prime } = 3 \sqrt {x +3} \]

15014

\[ {}y^{\prime } = 3 \sqrt {x +3} \]

15015

\[ {}y^{\prime } = x \,{\mathrm e}^{-x^{2}} \]

15016

\[ {}y^{\prime } = \frac {x}{\sqrt {x^{2}+5}} \]

15017

\[ {}y^{\prime } = \frac {1}{x^{2}+1} \]

15018

\[ {}y^{\prime } = {\mathrm e}^{-9 x^{2}} \]

15019

\[ {}x y^{\prime } = \sin \left (x \right ) \]

15020

\[ {}x y^{\prime } = \sin \left (x^{2}\right ) \]

15021

\[ {}y^{\prime } = \left \{\begin {array}{cc} 0 & x <0 \\ 1 & 0\le x \end {array}\right . \]

15022

\[ {}y^{\prime } = \left \{\begin {array}{cc} 0 & x <1 \\ 1 & 1\le x \end {array}\right . \]

15023

\[ {}y^{\prime } = \left \{\begin {array}{cc} 0 & x <1 \\ 1 & 1\le x <2 \\ 0 & 2\le x \end {array}\right . \]

15024

\[ {}y^{\prime }+3 x y = 6 x \]

15025

\[ {}\sin \left (x +y\right )-y y^{\prime } = 0 \]

15026

\[ {}y^{\prime }-y^{3} = 8 \]

15027

\[ {}x^{2} y^{\prime }+x y^{2} = x \]

15028

\[ {}y^{\prime }-y^{2} = x \]

15029

\[ {}y^{3}-25 y+y^{\prime } = 0 \]

15030

\[ {}\left (x -2\right ) y^{\prime } = 3+y \]

15031

\[ {}\left (y-2\right ) y^{\prime } = x -3 \]

15032

\[ {}y^{\prime }+2 y-y^{2} = -2 \]

15033

\[ {}y^{\prime }+\left (8-x \right ) y-y^{2} = -8 x \]

15034

\[ {}y^{\prime } = 2 \sqrt {y} \]

15035

\[ {}y^{\prime } = 3 y^{2}-y^{2} \sin \left (x \right ) \]

15036

\[ {}y^{\prime } = 3 x -y \sin \left (x \right ) \]

15037

\[ {}x y^{\prime } = \left (x -y\right )^{2} \]

15038

\[ {}y^{\prime } = \sqrt {x^{2}+1} \]

15039

\[ {}y^{\prime }+4 y = 8 \]

15040

\[ {}y^{\prime }+x y = 4 x \]

15041

\[ {}y^{\prime }+4 y = x^{2} \]

15042

\[ {}y^{\prime } = x y-3 x -2 y+6 \]

15043

\[ {}y^{\prime } = \sin \left (x +y\right ) \]

15044

\[ {}y y^{\prime } = {\mathrm e}^{x -3 y^{2}} \]

15045

\[ {}y^{\prime } = \frac {x}{y} \]

15046

\[ {}y^{\prime } = y^{2}+9 \]

15047

\[ {}x y y^{\prime } = y^{2}+9 \]

15048

\[ {}y^{\prime } = \frac {1+y^{2}}{x^{2}+1} \]

15049

\[ {}\cos \left (y\right ) y^{\prime } = \sin \left (x \right ) \]

15050

\[ {}y^{\prime } = {\mathrm e}^{2 x -3 y} \]

15051

\[ {}y^{\prime } = \frac {x}{y} \]

15052

\[ {}y^{\prime } = 2 x -1+2 x y-y \]

15053

\[ {}y y^{\prime } = x y^{2}+x \]

15054

\[ {}y y^{\prime } = 3 \sqrt {x y^{2}+9 x} \]

15055

\[ {}y^{\prime } = x y-4 x \]

15056

\[ {}y^{\prime }-4 y = 2 \]

15057

\[ {}y y^{\prime } = x y^{2}-9 x \]

15058

\[ {}y^{\prime } = \sin \left (y\right ) \]

15059

\[ {}y^{\prime } = {\mathrm e}^{y^{2}+x} \]

15060

\[ {}y^{\prime } = 200 y-2 y^{2} \]

15061

\[ {}y^{\prime } = x y-4 x \]

15062

\[ {}y^{\prime } = x y-3 x -2 y+6 \]

15063

\[ {}y^{\prime } = 3 y^{2}-y^{2} \sin \left (x \right ) \]

15064

\[ {}y^{\prime } = \tan \left (y\right ) \]

15065

\[ {}y^{\prime } = \frac {y}{x} \]